2009
DOI: 10.1002/pmic.200800604
|View full text |Cite
|
Sign up to set email alerts
|

The hemolymph proteome of the honeybee: Gel‐based or gel‐free?

Abstract: The honeybee has an invaluable economic impact and is a model for studying immunity, development and social behavior. The recent sequencing and annotation of the honeybee genome facilitates the study of its hemolymph, which reflects the physiological condition and mediates immune responses. We aimed at making a proteomic reference map of honeybee hemolymph and compared gel-free and gel-based techniques. One hundred and four 2-DE spots corresponding to 62 different proteins were identified. Eight identical 2-DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 58 publications
4
61
1
Order By: Relevance
“…This finding is in agreement with a recent investigation of soybean under flooding stress, where only 9 out of 115 proteins were detected by both gel-based and gel-free proteomics approaches in root tips (Yin et al, 2014). Similar results have been shown in the analysis of the honey bees hemolymph proteome, where only 27% of proteins were detected with both approaches (Bogaerts et al, 2009). …”
Section: Discussionsupporting
confidence: 85%
“…This finding is in agreement with a recent investigation of soybean under flooding stress, where only 9 out of 115 proteins were detected by both gel-based and gel-free proteomics approaches in root tips (Yin et al, 2014). Similar results have been shown in the analysis of the honey bees hemolymph proteome, where only 27% of proteins were detected with both approaches (Bogaerts et al, 2009). …”
Section: Discussionsupporting
confidence: 85%
“…In honey bees, however, conventional heat-inactivation steps and protease inhibitor cocktails commonly used in proteomic sample preparations do not completely 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 inhibit these activities 40 and this could lead to missed peptides. As well, several proteases have been described in neural tissue, 41 the venom sac 10 and hemolymph, 42 but the effect of endogenous protease activity on global protein degradation during protein extraction and preparation has not been investigated in tissues other than the gut. When examining other tissues, the gut is typically removed to eliminate the impact of proteases on sample integrity.…”
Section: Dynamic Range Genetic Variability Proteolysis and Ptms Arementioning
confidence: 99%
“…Feng et al (2014) found Idgf4 to be up-regulated in the hemolymph of both A. mellifera and A. cerana from the larval to the pupal stage (Feng et al 2014). Relatively strong spots of Idgf4 were identified in winter (Erban et al 2013) and summer (Bogaerts et al 2009) honeybee hemolymph. Even though Idgf4 is apparently present (used) throughout the life cycle of honeybee workers, its exact functions remain unknown.…”
Section: Chitinase-like Protein Idgf4 Is Constantmentioning
confidence: 99%
“…Zheng et al (2011) detected Obp13 and 14 during A. mellifera pupal head development. Obp13, 14, 15, and chemosensory protein 3 (ASP3) were identified in the hemolymph of A. mellifera summer workers (Bogaerts et al 2009), and Obp14 was found in winter worker hemolymph (Erban et al 2013). Briand et al (2002) observed that CSP3 is a brood pheromone carrier in A. mellifera .…”
Section: Olfaction-odorant-binding and Chemosensory Proteinsmentioning
confidence: 99%